Epoxidation of Alkenes with Molecular Oxygen as the Oxidant in the Presence of Nano-Al2O3 - Zhou, Xuan; Wang, Qiong; Xiong, Wenfang; Wang, Lu; Ye, Rongkai; Xiang, Ge; Qi, Chaorong; Hu, Jianqiang (Synlett, 2020)
The nano-Al2O3-promoted epoxidation of alkenes with molecular oxygen as the oxidant has been developed, providing an efficient route to a variety of epoxides in moderate to excellent yields. The environmentally friendly and efficient nano-Al2O3 catalyst could be easily recovered and reused five times without significant loss of activity.
Keywords: alkenes; nano-alumina; epoxidation; epoxides; molecular oxygen